Ferrogels based on entrapped metallic iron nanoparticles in a polyacrylamide network: extended Derjaguin–Landau–Verwey–Overbeek consideration, interfacial interactions and magnetodeformation. Issue 18 (20th April 2017) - Shankar, Ajay; Safronov, Alexander P.; Mikhnevich, Ekaterina A.; Beketov, Igor V.; Kurlyandskaya, Galina V.
Abstract : A new kind of ferrogel with entrapped metallic iron nanoparticles causing unusual magnetodeformation is presented. Abstract : A new kind of ferrogel with entrapped metallic iron nanoparticles causing unusual magnetodeformation is presented. Crosslinked polyacrylamide (PAAm) based ferrogels embedded with iron nanoparticles (MNPs) were synthesized by free radical polymerization in aqueous medium. Spherical iron MNPs with average diameter 66 nm were synthesized by the electrical explosion of wire and modified by interfacial adsorption of linear polyacrylamide (LPAAm). Extended Derjaguin–Landau–Verwey–Overbeek (xDLVO) calculations based on the superposing of van der Waals, electrostatic, steric, and magnetic contributions showed that polymeric encapsulation of nanoparticles by LPAAm is one of the most suitable pathways for preparing stable aqueous dispersions of iron nanoparticles. Microcalorimetry confirmed the presence of strong interfacial adhesion forces between LPAAm chains and the surface of iron nanoparticles. By keeping the same crosslinking density of a polymer network ( i.e. 100 : 1, monomer to crosslinker ratio) and varying the initial monomer concentration, an influence of the extent of polymer network reticulation on the mechanical properties and subsequently, magneto-elastic properties was demonstrated. It was found that the upper limit of the shear modulus for the synthesis of a new kind of polyacrylamide based ferrogel to exhibit any usable magnetodeformation under the application of a uniform external magnetic field of 420 mT is ca. 1 kPa. Magnetodeformation of cylindrical ferrogel samples was observed in the form of an overall volume contraction accompanied by a homogeneous decrease in all dimensions. The deformation was found to be maximum (around 10%) for the aspect ratio of 1/1 and it was lower and similar for the samples with 1/2 and 2/1 aspect ratios. Such a type of magnetic response is significantly different from the behavior observed in the existing reports on ferroelastomers.